The Efforts of Akidah Akhlak Teachers in Shaping Students’ Character at MI Maraqita’limat Mamben Lauk in the Academic Year 2024/2025 - Sri Muliani Ermadani; Mukammal; Sumiatun (Formad English Foundation NTB Jakarta, 2025)
This study explores the efforts of Akidah Akhlak teachers in shaping students’ character at MI Maraqita’limat Mamben Lauk during the 2024/2025 academic year. Character education plays a crucial role in developing students’ moral integrity, discipline, and social responsibility, particularly within Islamic educational settings where teachers serve as both moral educators and role models. The study aimed to identify the strategies used by teachers in character formation and to examine the supporting and inhibiting factors influencing these efforts. A qualitative descriptive approach was employed using a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the teachers’ efforts included integrating moral values into learning activities, modeling ethical behavior, habituating good practices, applying persuasive and disciplinary approaches, and collaborating with parents and the community. Supporting factors comprised teacher exemplarity, a conducive school environment, parental involvement, and curriculum-based moral integration, while inhibiting factors included lack of family support, negative media influence, and high teacher workload. The study concludes that successful character formation requires consistency, collaboration, and the embodiment of Islamic values by teachers. These findings contribute to the theoretical development of Islamic character education and offer practical insights for enhancing teacher strategies in fostering akhlaq al-karimah.